Nonlinear impacts of energy consumption and globalization on ecological footprint: Empirical research from BRICS countries. (10th April 2023) - Sun, Qingru; Ma, Ruxia; Xi, Zenglei; Wang, He; Jiang, Ce; Chen, Hanyu
Abstract: Exploring the influencing factors of ecological footprint is a hot issue. However, the impacts of energy consumption and globalization on ecological footprint are inconclusive due to the complex and nonlinear relationships among variables. The objective of this paper is to explore the nonlinear effects of energy consumption and globalization on ecological footprint in BIRCS countries. The quantile-on-quantile approach is employed, and the results display that in China and India, energy consumption has a positive impact on ecological footprint at most quantiles, while in South Africa, the negative impact appears at most quantiles. Furthermore, a positive effect of globalization on the ecological footprint is found at the most quantiles of the ecological footprint in China, South Africa. For Brazil, India, and Russia, the negative impact occurs at most quantiles of the ecological footprint. Finally, some policy recommendations are presented for the BRICS to achieve long-term sustainability. Graphical abstract: Image 1 Highlights: A quantile-on-quantile method is used to explore the effects of energy consumption and globalization on ecological footprint. The impact of energy consumption and globalization on ecological footprint is heterogeneous among different quantiles. We provide some policy recommendations for the BRICS to achieve long-term sustainability.